2003
DOI: 10.1128/iai.71.10.5739-5749.2003
|View full text |Cite
|
Sign up to set email alerts
|

gp63 Homologues inTrypanosoma cruzi: Surface Antigens with Metalloprotease Activity and a Possible Role in Host Cell Infection

Abstract: gp63 is a highly abundant glycosylphosphatidylinositol (GPI)-anchored membrane protein expressed predominantly in the promastigote but also in the amastigote stage of Leishmania species. In Leishmania spp., gp63 has been implicated in a number of steps in establishment of infection. Here we demonstrate that Trypanosoma cruzi, the etiological agent of Chagas' disease, has a family of gp63 genes composed of multiple groups. Two of these groups, Tcgp63-I and -II, are present as high-copy-number genes. The genomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
123
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(127 citation statements)
references
References 53 publications
4
123
0
Order By: Relevance
“…Previous studies already showed that the gp63 from T. cruzi has a key role in parasite infection [3] and complement inhibition [55]. We identified 7 clusters of this protein, and most of the hits were found in the EVs from Y strain.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Previous studies already showed that the gp63 from T. cruzi has a key role in parasite infection [3] and complement inhibition [55]. We identified 7 clusters of this protein, and most of the hits were found in the EVs from Y strain.…”
Section: Discussionmentioning
confidence: 88%
“…Trypanosoma cruzi cell surface is covered by a wide range of molecules including members of trans -sialidase (TS/gp85), mucin-like glycoproteins, mucin-associated proteins (MASP) superfamilies, and proteases [1–3]. Those molecules are involved in attachment and invasion to the host’s cell by infective forms of the parasite [46].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, multiple isoforms of the endopeptidase gp63 (clan MA, family M8) family have been found as well as matrix metallopeptidases-like peptidases [98,99]. Recently, exopeptidases such as metallocarboxypeptidases were found in the cytoplasm of the parasite [100,101].…”
Section: Gp63 and Other Metallopeptidasesmentioning
confidence: 99%
“…cruzi expresses multiple isoforms of the gp63 family of metallopeptidases at all life stages [98]. A polyclonal antiserum against recombinant gp63 of T. cruzi (Tcgp63) was used as a tool in order to study Tcgp63 expression and localization in this parasite.…”
Section: Gp63mentioning
confidence: 99%
“…Metallopeptidases homologous to the gp63 of Leishmania spp. are present in T. cruzi, as well as two metallocarboxypeptidases belonging to the M32 family, before found only in prokaryotes (Bonaldo, 1991;Lowndes, 1996;Burleigh, 2002;Cuevas, 2003;Nogueira de Melo, 2004;Gutierrez, 2008;Niemirowicz, 2007;Niemirowicz, 2008;Kulkarni, 2009). The most abundant among these enzymes is cruzipain (Cz), also known as GP57/51 or cruzain (the recombinant catalytic domain of cruzipain) a cysteine peptidase (CP) expressed as a mixture of isoforms.…”
Section: Peptidasesmentioning
confidence: 99%